2022
DOI: 10.3389/fimmu.2021.826621
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of CCR5 in the Course of Influenza Infection: Exploring Treatment Opportunities

Abstract: Influenza is one of the most relevant respiratory viruses to human health causing annual epidemics, and recurrent pandemics. Influenza disease is principally associated with inappropriate activation of the immune response. Chemokine receptor 5 (CCR5) and its cognate chemokines CCL3, CCL4 and CCL5 are rapidly induced upon influenza infection, contributing to leukocyte recruitment into the airways and a consequent effective antiviral response. Here we discuss the existing evidence for CCR5 role in the host immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…CCR5 is a cell membrane protein that is a member of the G protein-coupled receptor superfamily and is one of the main coreceptors for HIV to invade human cells. In recent years, with in-depth study of CCR5, its role in a variety of diseases, including HIV, influenza, insulin resistance, and tumors, has been confirmed ( 27 29 ). At present, some studies report that CCR5 and its ligand CCL5 act as a complex to link other molecules upstream or downstream to exert biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…CCR5 is a cell membrane protein that is a member of the G protein-coupled receptor superfamily and is one of the main coreceptors for HIV to invade human cells. In recent years, with in-depth study of CCR5, its role in a variety of diseases, including HIV, influenza, insulin resistance, and tumors, has been confirmed ( 27 29 ). At present, some studies report that CCR5 and its ligand CCL5 act as a complex to link other molecules upstream or downstream to exert biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects were mediated via incorporation of CC chemokine receptors, which are members of the G protein-coupled receptor superfamily, on the cell surface. Previous studies have demonstrated that a combination of CCL3 or CCL5 and CCR5 might cause severe inflammation and damage in acute pancreatitis, inflammatory bowel disease, and lung tissue (20)(21)(22)(23). Thus, NK cells have a close relationship with the onset of a cytokine storm, which might explain why our patient had symptoms similar to HLH after therapy.…”
Section: Discussionmentioning
confidence: 69%
“…41,42 CCR5 is rapidly induced on T cells during acute respiratory viral infection, is critical to early migration of memory CD8+ T cells to the lungs 43,44 , and together with its ligands (CCL3, CCL4, CCL5) has been implicated in the pathogenesis of interstitial lung diseases and acute COVID-19 illness. [43][44][45][46][47][48][49] In accord, CCL4, along with CXCL9, another type 1 chemoattractant, was integral to inflammatory signatures of patients in group D. Although CXCR3, the receptor for CXCL9, was not a prominent feature in the blood, low levels were expressed on T cells present in the lungs of COVID patients (Mc1, CD8+ TEM), suggesting its upregulation in lung tissue where it may contribute to tissue repair or else promote virus-induced lung pathology. 50,51 CXCR3 was also expressed on "effector-like" naïve CD8+ T-cells that were chronically depleted in the blood, most likely reflecting their egress out of circulation for participation in the T-cell response.…”
Section: Discussionmentioning
confidence: 88%